The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.21273/jashs.115.6.915
|View full text |Cite
|
Sign up to set email alerts
|

Fruit Growth and Development of `Ideal' and `Western' Pecans

Abstract: Pecan [Carya illinoensis (Wangenh.) K. Koch] fruit development was evaluated over three growing seasons (1981-83) to determine the seasonal growth patterns in the cultivars Ideal and Western. Gross morphological stages were examined weekly in fruit dissected in cross and longitudinal sections. Free-nucleate endosperm was first observed in mid-July when fruit had grown to 50% of their final length, occurring at 67 days after stigma receptivity (DASR) for 'Ideal' and 76 DASR for Western'. Maximum content of free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…7; Table 2). Herrera (1990) and Wells et al (2007) concluded that low soil moisture during the kernel-filling stage reduces embryo development and kernels do not fill properly. However, our yield data were a case study and we had no mechanism for estimating error.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7; Table 2). Herrera (1990) and Wells et al (2007) concluded that low soil moisture during the kernel-filling stage reduces embryo development and kernels do not fill properly. However, our yield data were a case study and we had no mechanism for estimating error.…”
Section: Discussionmentioning
confidence: 99%
“…Pecan nut development can be divided into two stages: nut sizing and kernel filling (Wells et al, 2007). In nut sizing, the nut enlarges and the volume of endosperm increases (Herrera, 1990). Water deficit during nut sizing diminishes the ability of pecan roots to extract soil water and this reduces growth and nut size and increases nut split (Wells et al, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Trees in orchards mismanaged irrigation show low production (0.8 t ha -1 ) and quality (glued husk, walnut germination and lack of fruit filling), which is associated with water stress caused by improper programming irrigation, mainly for almond filling (Stein et al, 1989;Herrera, 1990;Sparks, 1995c).…”
Section: Materiales Y Métodosmentioning
confidence: 99%
“…Los árboles de las huertas en riegos mal manejados, muestran baja producción (0.8 t ha -1 ) y calidad (ruezno pegado, germinación de la nuez y falta llenado de fruto), que está asociado con estrés hídrico causado por una inadecuada programación de los riegos principalmente en llenado de almendra (Stein et al, 1989;Herrera, 1990;Sparks, 1995c).…”
Section: Introductionunclassified